2015
DOI: 10.1155/2015/108029
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Dysfunction andα-Synuclein Synaptic Pathology in Parkinson’s Disease: Who’s on First?

Abstract: Parkinson's disease (PD) is the most common neurodegenerative movement disorder. Its characteristic neuropathological features encompass the loss of dopaminergic neurons of the nigrostriatal system and the presence of Lewy bodies and Lewy neurites. These are intraneuronal and intraneuritic proteinaceous insoluble aggregates whose main constituent is the synaptic protein α-synuclein. Compelling lines of evidence indicate that mitochondrial dysfunction and α-synuclein synaptic deposition may play a primary role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
58
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 133 publications
3
58
0
1
Order By: Relevance
“…The loss of GBA activity promotes SNCA accumulation by inhibiting lysosomal function, whereas direct interactions between mutant GBA and SNCA promote SNCA aggregation [71]. Additionally, impaired mitochondrial homeostasis may interact with SNCA deposition to form a ‘vicious cycle’, in which SNCA accumulation increases mitochondrial permeability [72,73] and mitochondrial ROS generation, which further promotes SNCA misfolding, aggregation, and accumulation [73]. We propose that, as a predisposing factor, heterozygous GBA mutations may contribute to the risk of PD by conferring a distinct subclinical pathological state with mitochondrial dysfunction and autophagy defects, which lowers the threshold and increases the risk for SNCA accumulation, ultimately culminating in the development of PD.…”
Section: Discussionmentioning
confidence: 99%
“…The loss of GBA activity promotes SNCA accumulation by inhibiting lysosomal function, whereas direct interactions between mutant GBA and SNCA promote SNCA aggregation [71]. Additionally, impaired mitochondrial homeostasis may interact with SNCA deposition to form a ‘vicious cycle’, in which SNCA accumulation increases mitochondrial permeability [72,73] and mitochondrial ROS generation, which further promotes SNCA misfolding, aggregation, and accumulation [73]. We propose that, as a predisposing factor, heterozygous GBA mutations may contribute to the risk of PD by conferring a distinct subclinical pathological state with mitochondrial dysfunction and autophagy defects, which lowers the threshold and increases the risk for SNCA accumulation, ultimately culminating in the development of PD.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulation of iron in substantia nigra contributes to the cell death by enhancing lipid peroxidation, as judged by raised levels of both malondialdehyde and lipid hydroperoxides (Hauser et al 2013;Ward et al 2015). But the hippocampus is the most vulnerable area to oxidative stress, it was demonstrated that an early event in the course of dopamine depletion following 6-OHDA administration is the generation of oxidative stress in the hippocampus and it caused memory impairment (Hritcu et al 2011;Sriraksa et al 2012;Zaltieri et al 2015). The post-mortem studies from PD patients suggested the involvement of an excess formation of free radicals and the onset of oxidative stress in the disease progression (Ren et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…• A build up of toxic proteins in the brain (Lansbury et al, 2006;Majd et al, 2015;Zaltieri et al, 2015) • A loss of mitochondrial function that leads to the oxidative stress and creation of neurotoxic molecules that trigger cell death (apoptotic, necrotic or autophagy) Betarbet et al,2000;Zhu and Chu, 2010) • Changes in the levels and activities of neurotrophic factors (Zuccato and Cattaneo, 2009;Michalski et al, 2015) • Variations in the activity of neural networks Kann, 2015;Sala-Llonch et al, 2014).…”
Section: Tissuementioning
confidence: 99%
“…However, the causative link between mitochondrial dysfunction and its relationship to protein degradation and intracellular transport is well documented (Zaltieri et al, 2015). The dynamic nature of protein aggregation means that, despite progress towards understanding aggregation, its relationship to disease is difficult to determine in the laboratory.…”
Section: Tissuementioning
confidence: 99%
See 1 more Smart Citation